Human Umbilical Cord Blood Cells Induce Neuroprotective Change in Gene Expression Profile in Neurons after Ischemia through Activation of Akt Pathway. Issue 4 (April 2015) - Shahaduzzaman, M. D.; Mehta, Vijay; Golden, Jason E.; Rowe, Derrick D.; Green, Suzanne; Tadinada, Ramya; Foran, Elspeth A.; Sanberg, Paul R.; Pennypacker, Keith R.; Willing, Alison E.
Human umbilical cord blood (HUCB) cell therapies have shown promising results in reducing brain infarct volume and most importantly in improving neurobehavioral function in rat permanent middle cerebral artery occlusion, a model of stroke. In this study, we examined the gene expression profile in neurons subjected to oxygen-glucose deprivation (OGD) with or without HUCB treatment and identified signaling pathways (Akt/MAPK) important in eliciting HUCB-mediated neuroprotective responses. Gene chip microarray analysis was performed using RNA samples extracted from the neuronal cell cultures from four experimental groups: normoxia, normoxia + HUCB, OGD, and OGD + HUCB. Both quantitative RT-PCR and immunohistochemistry were carried out to verify the microarray results. Using the Genomatix software program, promoter regions of selected genes were compared to reveal common transcription factor-binding sites and, subsequently, signal transduction pathways. Under OGD condition, HUCB cells significantly reduced neuronal loss from 68% to 44% [one-way ANOVA, F (3, 16) = 11, p = 0.0003]. Microarray analysis identified mRNA expression of Prdx5, Vcam1, CCL20, Alcam, and Pax6 as being significantly altered by HUCB cell treatment. Inhibition of the Akt pathway significantly abolished the neuroprotective effect of HUCB cells [one-way ANOVA, F (3, 11) = 8.663, p = 0.0031]. Our observations show that HUCB neuroprotection is dependent on the activation of the Akt signaling pathway that increases transcription of the Prdx5 gene. We concluded that HUCB cell therapy would be a promising treatment for stroke and other forms of brain injury by modifying acute gene expression to promote neural cell protection.